Layperson Ability and Willingness to Use Hemostatic Dressings: A Randomized, Controlled Trial. (2nd November 2019) - Goolsby, Craig; Rojas, Luis; Moore, Krista; Kretz, Eric; Singletary, Eunice; Klimczak, Victoria; Charlton, Nathan
Abstract: Background: The Hartford Consensus and Stop the Bleed Campaign empower the public to stop bleeding. While evidence for civilian tourniquet use is mounting, there is limited evidence regarding the public's ability to use hemostatic dressings. This study seeks to determine if laypeople can apply hemostatic dressings, and which hemostatic dressing they can use most successfully. Methods: 360 layperson participants in Maryland and Virginia completed 4 arms of this randomized, prospective controlled trial: plain gauze (control), z-folded gauze, s-rolled gauze, and injectable sponge (experimental) arms. Participants watched a standardized video, practiced hands-on dressing application, and were assessed applying the dressing via checklists and feedback mechanisms for pressure, timing, and packing. Participants completed pre and post questionnaires regarding willingness to use hemostatic dressings. Results: Overall, 202 participants (56%) applied the dressings correctly, and 83 (92%) applied the injectable sponges correctly. This is a significant difference from the other arms (p < 0.001), and OR 17.2 (95% CI 6.8 – 48.1) compared to control. 38 participants (40%) correctly applied plain gauze, while 37 (43%) and 44 (48%) participants correctly applied z-folded and s-rolled gauzes. The primary reasons for failure were not holding pressure long enough (n = 103, 65%) and not applying adequate pressure (n = 64, 41%). Participants in all arms had significant improvements in willingness to use hemostatic dressings: 154 (43.6%) participants pre vs. 344 (97.5%) post study participation (p < 0.001). Conclusions: More than half of laypeople can apply hemostatic dressings, and they are most successful applying injectable sponges. Brief education increases laypeople's reported willingness to use hemostatic dressings. Educators and planners should consider including injectable sponges in their Stop the Bleed programs and products. Level of Evidence: II (RCT with significant difference. One negative criterion for observer blinding).